Wakatobi Development Priorities as A Sustainable Tourism Destination Using the Analytical Hierarchy Process Method - Putu Edi Dimas Saputra; I Gusti Ayu Made Srinadi; Made Susilawati; I Putu Eka Nila Kencana; Made Ayu Dwi Octavanny; G. K. Gandhiadi (International Journal of Educational Research, 2024)
Wakatobi is one of the tourist destinations renowned for its underwater beauty, holding great potential to be developed as a sustainable tourism destination. This research aims to determine the priorities for sustainable tourism development in Wakatobi using the Analytical Hierarchy Process (AHP) method. The AHP method is employed to identify and prioritize various criteria and sub-criteria contributing to sustainable tourism development. Based on the research findings, infrastructure and facilities were found to be the highest priorities, with a focus on improving transportation infrastructure and public facilities. These findings indicate that the development of transportation infrastructure and public facilities is crucial to support the sustainability of tourism in Wakatobi.